A piece of art in the Belarusian media art discourse: interpretive statues and value orientations - Tochitskaya, Nadezhda A. (Journal of the Belarusian State University. Journalism, 2020)
Defines the main interpretive strategies of a piece of art in the Belarusian media art discourse, considers the interpretation from the axiological point of view. Interpretation is an important step in the process of understanding a piece of art. It is subjective in nature and helps to explain reality. Objective factors are not exhausted by the external relations of a piece of art with reality and culture. The internal connections of the work as well as its social functioning are of equal importance. All these factors determine the accuracy of the meaning of a piece of art, despite the multiplicity and variability of its interpretations. Among researchers there is no general idea about the essence of interpretation in the Belarusian media art discourse and interpretation strategies, which is a problem. With the help of the analysis of the researches of interpretation in philosophy, literature and materials of Belarusian mass and specialized editions the main interpretive strategies were singled out. The restorative strategy allows to destroy in the consciousness of the audience stereotypes that have appeared around Belarusian literature and cinematography. Due to the implementation of this strategy a positive image of the above mentioned kinds of art is created in Belarusian publications. The analytical strategy, which is more typical for theatrical art, is aimed at comprehending a piece of art in a new mentality. When interpreting a piece of art, it is possible to use not only hermeneutic approach, but also axiological one, which makes it possible to express the content of a piece of art through the category of value. The interpreter is able to see values even in a work that is destructive in its content, which can also be considered as an interpretive strategy.